Mesenchymal stem cells act as stimulators of neurogenesis and synaptic function in a rat model of Alzheimer's disease - Maryam Doshmanziari; Sadegh Shirian; Mohammad-Reza Kouchakian; Seyedeh Farzaneh Moniri; Saranaz Jangnoo; Niloofar Mohammadi; Fariba Zafari (Heliyon, 2021)
Background: Alzheimer's disease (AD) is one of the most common NDs leading to cognitive dysfunctions and dementia which are progressively worsen with age. Cell therapy is currently of particular interest in treatment of neurodegenerative disease (ND) such as AD. However, the effective treatment for AD is yet to be found. Objective: In this study, the possible roles of human umbilical mesnchymal stromal cord (hUMSCs) and adipose mesenchymal stem cells (hAD-MSCs) in neurogenesis and synaptic function were investigated using a β-amyloid 1–42 (β A42)-induced AD rat model. Methods: hUMSCs and hAD-MSCs were isolated from umbilical cord stroma and adipose tissue, respectively. The expression of Mesenchymal (CD73, CD90 and CD105) and hematopoietic (CD45 and CD133) markers of hUMSCs and hAD-MSCs were confirmed by flow cytometry. Alzheimer's rat model was created by β-amyloid 1–42 injection into the hippocampus and confirmed by Morris Water Maze and immunohistochemical staining. hUMSCs and hAD-MSCs were injected in Alzheimer's rat model, intravenously. Deposition of β-amyloid in the CA1 of hippocampus was assayed 3 months after cell administration. The expression of synaptophysin and GAP43 proteins was assessed by Western blot. Neural death was assessed by Nissl staining. Results: The data obtained from flow cytometry showed that surface mesenchymal and hematopoteic markers of the fibroblastic like cells isolated from adipose tissue and umbilical cord were expressed highly in hUMSCs and mostly in hAD-SCs. Transplantation of MSCs reduced β-amyloid deposition in the hippocampus of the AD rats compared to the β-amyloid group. The rate of neuronal cell death in the hippocampus of the β-amyloid-treated rats was significantly increased compared to that of the control group. The percentage of apoptotic cells in this group was 72.98 ± 1.25, which was significantly increased compared to the control group. Transplantation of either hUMSCs or hAD-SCs, respectively, resulted in a significant reduction in the apoptotic rate of the neuronal cells in the hippocampus by 39.47 ± 0.01 (p = 0.0001) and 43.23 ± 0.577 (p = 0.001) compared to the β-amyloid group. MSC transplantation resulted in a significant up-regulation in the expression levels of both synaptogenic (synaptophysin) and neurogenic markers (GAP43) by 1.289 ± 0.112 (P = 0.02) and 1.112 ± 0.106 (P = 0.005) fold in the hUMSCs-treated group and 1.174 ± 0.105 (P = 0.04) and 0.978 ± 0.167 (P = 0.008) fold in the hAD-SCs-treated group, respectively. Conclusion: Intravenous injection of hUMSCs and hAD-MSCs is a safe approach that improves synaptic function and neurogenesis via up-regulation of synaptophysin and GAP43 protein expression levels, respectively, in Alzheimer's model. Intravenous injection of both applied SCs could improve learning and cognitive impairment induced by β A42 injection.